Perlindungan Hukum terhadap Kesehatan dan Keselamatan Kerja Karyawan PT. PLN ULTG Kudus - Moch Rudi,Hengky widiatmoko, Iskandar Wibawa (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2025)
This study aims to determine the legal protection of Health and safety of employees of PT PLN ULTG Kudus in terms of employee rights, especially the right to protection of Occupational Safety and health. Legal protection of Occupational Safety and health of PT PLN ULTG Kudus employees is going well, especially through efforts such as the provision of personal protective equipment in the form of personal protective equipment, health insurance and labor. In addition, there are also consulting services, professional training and employee supervision supervision. Some of the obstacles identified include inconsistencies in the use of personal protective equipment by employees during work. Hospital facilities registered by the company are still limited. The company's efforts include periodic monitoring of work performance and sending requests to customer hospitals in the region.